DAKWAH DALAM PLURALISME BERAGAMA - Fifi Novianty (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
This journal wants to explain about Da'wah in the midst of religious pluralism brought by KH.A Syatori at the Dar Al-Tauhid Arjawinangun Islamic Boarding School in Cirebon bringing positive positive social relations between students and the community, both Muslim and non-Muslim. In addition to focusing heavily on the process of learning the Qur'an, KH A Syatori also always informs students of the Dar Al-Tauhid Arjawinangun Islamic Boarding School to be interconnected between religious communities, while the religious environment of the students diverts this matter inseparable from the influence of education applied by KH. A Syatori The results of the study said that the figure who was the pioneer of Islamization in the midst of religious pluralism in the Dar Al-Tauhid Arjawinangun Islamic Boarding School was KH. A Syatori has proven to his people that Islam is a religion that will increase the level of understanding and can unite with other non-Muslims to create a beautiful religious harmony in the environment of Dar Al-Tauhid Arjawinangun Islamic Boarding School. And the da'wah pluralism has brought influence in the fields of Economy, Social, Politics, and Culture.